The 5E Learning Cycle Model Assisted by Mind Mapping on the Learning Outcomes of IPAS for Fifth-Grade Students - Ketut Risa Intania; I Gede Margunayasa; Ni Putu Kusuma Widiastuti (Mimbar Ilmu, 2025)
The low learning outcomes of fifth-grade students in the subject of IPAS (Integrated Science and Social Studies) have become a fundamental problem in the learning process. One of the contributing factors is the limited variety of learning models and the lack of active student engagement. This study aims to examine the effect of implementing the 5E Learning Cycle model assisted by Mind Mapping on students’ learning outcomes. The study employed a quasi-experimental approach with a Nonequivalent Post-test Only Control Group Design. The subjects consisted of 41 students divided into an experimental group and a control group. Data were collected using objective tests as instruments to measure learning outcomes. Data analysis was conducted using descriptive statistics and inferential t-tests. The analysis results showed a significance value (Sig. 2-tailed) of 0.000 < 0.05, indicating a significant difference between the learning outcomes of students taught using the 5E Learning Cycle model assisted by Mind Mapping and those who were not. The study concludes that the implementation of an innovative and visually-based learning model has a significant impact on improving IPAS learning outcomes. The implications of these findings highlight the importance of employing learning approaches that encourage active student engagement to achieve more optimal learning outcomes.